Attitudes of Caregivers of Older Thai Adults with Major Depression: A Qualitative Study - Chankham, Wariya; Rangsiman Soonthornchaiya; Pranom Othaganont; Jing Jy Wang (Pacific Rim International Journal of Nursing Research, 2023)
Family caregivers are essential people. They are the primary source of support and care for the person they are caring for, and such care is reflected in and affected by their attitudes. This qualitative descriptive study explored 17 primary family caregiv- ers’ attitudes toward caring for older adults with a major depressive disorder living at home in Thailand. Purposive sampling was undertaken, and data were collected in semi-structured interviews and analyzed using content analysis. As a result, two themes emerged. The first theme, “Rethinking in positive ways about caregiving,” included accepting being a caregiver and feeling happy and proud to provide care for a loved one. The second theme, “Began with negative attitudes towards caregiving,” included uncertainty about life, feelings of suffering, and frustration with caregiving duties. The caregivers met with challenges, and their attitudes directly affected the care they provided to older adults with major depressive disorders. Therefore, nurses and other healthcare professionals need to understand caregiving better, positively and acceptably, to improve caregivers’ ability to manage depressive symptoms. Caregiving will be enhanced by educating and training families and health professionals on effective care techniques and mentoring families in the early stages of caring for older adults with depressive disorders and throughout the care.